Rapid screening for selection of heavy metal-tolerant plants - Piotto,Fernando Angelo (2014)
One of the major difficulties in studies on the selection of heavy metal tolerant plants is the proper methodology that must ensure an efficient evaluation of a large number of plants, but reducing environmental contamination. For this reason, we propose a simple and effective method that can be applied to metals or other chemicals by means of a case study, in which we selected two cadmium-tolerant mutants of tomato (cv Micro-Tom) obtained by mutagenesis with methyl ethanesulfonate (MES). Aside from these two new mutants, we selected 21 others with possible alterations in the response to this metal. Finally, it was concluded that the proposed system is ideal for selection studies on plants tolerant to heavy metals and possibly to other elements, due to the ease of assembly of the structure, low installation cost, minimal waste generation and the possibility of using different species and heavy metals.